IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILIY DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Suryadi, Andy (Jurnal Ilmu Administrasi Negara, 2016)
Implementation of Corporate Social Responsibility Program in Enhancing Community Welfare. The purpose of this study is to investigate the implementation of corporate social responsibility program at PT. Arara Abadi in improving the welfare of the community. Informants in this study are implementing corporate social responsibility program of PT. Arara Abadi and village government officials, village communities. Data collection technique were interview, observation and documentation. Analysis of data through the process of presenting the data, data reduction and conclusion. The research found that the implementation of corporate social responsibility program at PT. Arara Abadi in improving the welfare of people in Pelalawan 2015 has been running pretty well. But the benefits of this program can not be enjoyed by the whole group policy goals.